Pemberdayaan Ibu Hamil melalui Edukasi tentang Akupressur untuk Peningkatan Produksi ASI - Nurbaiti, Nurbaiti; Gustina, Gustina; Perwitasari, Tuhu; Nurita, Suci Rahmani (Universitas Baiturrahim, 2025)
Breast milk contains high nutrients that are very beneficial for health, infant development in order to achieve optimal growth. The number of exclusive breastfeeding presentations in Jambi province in 2023 was 65.66%, and in Jambi City it was 57.92%, the impact of babies not being given exclusive breastfeeding in infants aged 0-6 months can cause diseases such as infections, respiratory tract and diarrhea. The obstacles for mothers in providing exclusive breastfeeding such as lack of knowledge, work, mothers feel stressed, tired, and breast milk is not smooth. The purpose of this community service activity is to increase the knowledge of pregnant women about acupressure to increase breast milk production, the target in this activity is 30 pregnant women, the details of the activities arepre-test carried out for 10 minutes, education is carried out for ±90 minutes using lecture, discussion and question and answer methods using leaflet media, carrying out evaluations by providingpost-test for 10 minutes. The results of the evaluation were then analyzed to determine changes in respondents' knowledge related to the material presented, namely about acupressure in increasing breast milk production. After educating pregnant women, there was an increase in mothers' knowledge about the benefits of acupressure to increase breast milk production by 23.3%. It is hoped that the material that has been presented can be applied independently by pregnant women in preparing for their lactation period, and can disseminate information to family and relatives so that the exclusive breastfeeding program can be achieved.